Novel Opiate-Free Anesthetic Technique for Major Urologic Procedures. Issue 10 (October 2020) - Smith, Susan A.; Ghabra, Hussam; Dhaifallah, Daniah G.; Rahnema, Alexander; Evans, Bryan M.; Nossaman, Bobby D.; Sumrall, William D.; Bardot, Stephen F.; Canter, Daniel J.
Abstract : Objectives: We postulated that an opiate-free (OF) general anesthesia (GA) technique could adequately control a patient's pain without adversely affecting recovery. We compared patients undergoing major urologic procedures with and without opiate-based GA. Methods: A propensity-matched analysis was performed comparing hospital length of stay, postoperative nausea and vomiting, ileus occurrence, postanesthesia care unit, and total opiate consumption, as well as sedation and hemodynamic variables. The data are expressed as medians and were analyzed with the Wilcoxon rank-sum test. P < 0.05 indicate statistical significance. Results: In total, 166 patients were evaluated in both the OF group and the opiate-based treatment group. American Society of Anesthesiologists classification and age were comparable, with most surgeries being laparoscopic and confined to the bladder, kidney, and prostate gland. The median opiate consumption in morphine equivalents in the postanesthesia care unit was 7.7 mg (range 5–11.7 mg) for the OF cohort versus 11.7 mg (range 5–17.3 mg) for the control group ( P < 0.001). Similarly, the median total postoperative opiate consumption in morphine equivalents was 23.9 mg (range 13.8–42.4 mg) for the OF group compared with 32.1 mg (range 17.38–57.51 mg) for the control group ( P = 0.0081). The median hospital length of stay for the OF group was 1.4 days (range 1.2–2.3 days) versus 1.3 days (range 1.2–2.4 days) for the control group ( P = 0.8466). Conclusions: There was a statistically significant difference in opiate consumption postoperatively for patients who underwent an OF technique compared with a conventional opiate-based technique. This technique appears to be a possible alternative approach, without any apparent untoward consequences during admission. Abstract : Opioids are essential elements in the practice of anesthesia. This article provides an alternative general anesthetic technique to the conventional opioid-based anesthesia for abdominal surgeries—specifically, urologic procedures without apparent adverse outcomes.